2008
DOI: 10.1007/s10522-008-9179-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of stress signalling via p38 MAP kinase in the premature senescence of Ataxia Telangiectasia and Werner syndrome fibroblasts

Abstract: The premature ageing Ataxia Telangiectasia (AT) and Werner syndromes (WS) are associated with accelerated cellular ageing. Young WS fibroblasts have an aged appearance and activated p38 MAP kinase, and treatment with the p38 inhibitor SB230580 extends their lifespan to within the normal range. SB203580 also extends the replicative lifespan of normal adult dermal fibroblasts, however, the effect is much reduced when compared to WS cells, suggesting that WS fibroblasts undergo a form of stress-induced premature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…Thus, the WS-associated genetic defect is related to impaired maintenance of DNA integrity, and has implications for the presence of oxidative stress in the WS phenotype (von Kobbe et al 2004). The roles of oxidative stress in WS have been investigated in studies of WRNp functions (von Kobbe et al 2004;Bukowy et al 2008;Harrigan et al 2007), consistent with in vitro (Davis and Kipling 2009) and animal studies (Deschênes et al 2005;Massip et al 2006;Moore et al 2008). Our previous reports provided evidence for excess oxidative stress in blood cells and body fluids from WS patients versus controls and versus patients with other genetic diseases (Pagano et al 2005b;Lloret et al 2008a).…”
Section: The Ws-mitochondria Puzzlementioning
confidence: 72%
“…Thus, the WS-associated genetic defect is related to impaired maintenance of DNA integrity, and has implications for the presence of oxidative stress in the WS phenotype (von Kobbe et al 2004). The roles of oxidative stress in WS have been investigated in studies of WRNp functions (von Kobbe et al 2004;Bukowy et al 2008;Harrigan et al 2007), consistent with in vitro (Davis and Kipling 2009) and animal studies (Deschênes et al 2005;Massip et al 2006;Moore et al 2008). Our previous reports provided evidence for excess oxidative stress in blood cells and body fluids from WS patients versus controls and versus patients with other genetic diseases (Pagano et al 2005b;Lloret et al 2008a).…”
Section: The Ws-mitochondria Puzzlementioning
confidence: 72%
“…The latter is probably secondary to poor nutrition and early confinement to wheelchair. There is animal experimental evidence that ATM deficiency leads to an osteoporotic phenotype in mice due to reduced bone formation and increased bone resorption [33] or accelerated cellular ageing [34].…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
“…Thus, SB203580 essentially prevented the accelerated ageing seen in primary WS cells. SB203580 treatment had no, or minimally, significant effects on normal cells (for effects on growth rate and lifespan see Figure 8b) [88,101]­, so this finding suggested that the abnormal growth, enlarged morphology and premature senescence of WS cultures resulted from the activation of an SB203580-suppressible pathway. …”
Section: Use Of Mapk Inhibitors For the Treatment Of Werner Syndromementioning
confidence: 99%